Impediments to Delivering Oral Presentations in English among Malaysian ESP Undergraduates - Benraghda, Abdelmadjid; Noor Raha, Mohd Radzuan; Zuraina, Ali (2017)
A common issue faced by many undergraduates in the classroom is the requirement to deliver oral presentations in English. The current study investigates local and international undergraduates’ attitudes towards oral English presentations in class. Then, the correlation is examined between the undergraduates’ attitudes and their performance scores in oral presentation in English. Moreover, this study tries to shed some light on the problems hindering undergraduates in delivering oral presentation in the classrooms. Questionnaire and Semi-structured interviews were conducted with undergraduates at the Universiti Malaysia Pahang (UMP), Malaysia. The results show that the undergraduates possess a positive attitude towards oral English presentations. Additionally, a positive correlation is found between the students’ attitudes and their scores in oral presentation. The findings of the semi-structured interviews reveal a number of impediments exist in presenting orally in English. These hindrances include anxiety, poor English language proficiency and classroom atmosphere. The findings contribute to a better understanding of the nature of the undergraduates’ attitudes with regards to their oral performances in tertiary academic and professional spheres.